Redes de cooperação: um estudo sobre a criação e captura de valor por produtores de hortaliças no Oeste do Paraná - Raupp, Ivan Decker (2012)
The participation in horizontal cooperation networks is suggested by several authors as an important strategy so that low economic status farmers under family management can keep or improve the profitability of their entrepreneurships. In this context, the issue that guides this study is to answer whether the horizontal cooperation networks which are set up among the family producers of vegetables really allow them to aggregate value to production and whether the values occasionally aggregated are captured by them as well. In order to answer it, a theoretical matrix was used, where it is discussed the importance of the collective action and the cooperation networks as a governance structure which encourage the family agriculture and, thus, the rural development. In the empirical approach, a study of multi-case of two organizations was carried out, a cooperative and an association of producers that gathers vegetable producers. As a result, it is noticed that the strategies developed by means of both organizations allowed the farmers to have the aggregation and the value capture. The participation in the cooperative provided to the producers gains resulting from the transference of technology and scale extension in vegetable production. In regard to the association, the value aggregation mainly resulted from the access to more profitable distribution channels and from processes of product differentiation. In both cases, it is also evidenced the value capture translated by the extension of the farmers average income and other indicators described in this study as well. However, it was possible to identify that, in spite of the gains provided to the farmers, the studied organizations face problems of economic competitiveness and viability of the same ones which were pointed out in this study. On the basis of such information, at the end of this essay, some suggestions were formulated in order to contribute with the improvement of the farmers income and the sustainability of the studied organizations.